Tourism information system as a mechanism to promote ‎tourism services: An analytical study of the case of Algeria ‎‎(2000-2015)‎ - Yedou, Mohamed; ‏ BoukhariSoumia (Dirassat Journal Economic Issue, 2017)
Tourism now is one of the leading economic activities in the countries with important tourism sites, that are frequented and visited by tourists and stakeholders interested in the tourism industry and its projects. Therefore, the existence of a tourist information system in Algeria based on correct scientific bases; it represents the starting point for an effective tourism promotion, as it aims for attracting several tourists and convincing them to acquire tourism services, which further will raise the revenues which rationalize the productivity in the tourism industry sector.